Analgesic Activity of Chitosan in Arthritis Rats Induced by Complete Freund's Adjuvant (CFA) - Putri, Dwi Kurnia; Darmawan, Endang (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2022)
Arthritis is inflammation and pain in joints, often accompanied by stiffness and difficulty to move. The current pain treatment in arthritis is synthetic drugs that have many side effects. Chitosan’s structure similar to that of glucosamine which can be used as anti-arthritis. This study aims to evaluate the analgesic activity of chitosan in arthritic rats. The heat stimulation method with a hot plate at temperature of 55±1oC was utilized. A total of 25 male Sprague Dawley rats, weighing 150-250 g, were fed and given water ad libitum. There were grouped into group I (normal control), group II (positive control), group III (negative control, given diclofenac sodium), group IV and V (chitosan treatment at 50 and 100 mg/200g BW of rats, respectively). Arthritis in groups II to V rats were induced by subplantar injection of Complete Freund's Adjuvant (CFA) on the first day according to the Anderson method. Analgesic activity was measured every 3 days on day 17 onwards. The obtained data were analyzed using a general linear repeated measure test (p <0.05). The percentage of pain response reduction in normal control, positive control, negative control, chitosan group at 50 and 100 mg/200 g body weight (BW) were 0.30±1.73, -13.46±0.74, 20.37±1.54, 31.52±1.44, and 35.29±0.72%, respectively. Thus, chitosan can be used as an analgesic in arthritic rats.